2009
DOI: 10.1051/0004-6361/200811196
|View full text |Cite
|
Sign up to set email alerts
|

Observations of conduction driven evaporation in the early rise phase of solar flares

Abstract: Context. The classical flare picture features a beam of electrons, which were accelerated in a site in the corona, hitting the chromosphere. The electrons are stopped in the dense chromospheric plasma, emitting bremsstrahlung in hard X-rays. The ambient material is heated by the deposited energy and expands into the magnetic flare loops, a process termed chromospheric evaporation. In this view hard X-ray emission from the chromosphere is succeeded by soft-X-ray emission from the hot plasma in the flare loop, t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 51 publications
5
107
0
Order By: Relevance
“…The observed emissions require a major part of the flare energy, even though the impulsive-phase acceleration has not yet begun. Battaglia et al (2009) suggest that this phase proceeds via conduction-driven evaporation as a response to this energy input, which is presently not understood. We note that observations of source motions now are beginning to suggest the contraction of the coronal magnetic field in this phase (Hudson 2000); see also the discussion below in Sect.…”
Section: Early Phasementioning
confidence: 98%
“…The observed emissions require a major part of the flare energy, even though the impulsive-phase acceleration has not yet begun. Battaglia et al (2009) suggest that this phase proceeds via conduction-driven evaporation as a response to this energy input, which is presently not understood. We note that observations of source motions now are beginning to suggest the contraction of the coronal magnetic field in this phase (Hudson 2000); see also the discussion below in Sect.…”
Section: Early Phasementioning
confidence: 98%
“…For example, recently, Battaglia et al (2009) analyzed four flares and demonstrated that the morphology of these events showed one hot coronal source only, while the footpoints appeared much later, at the onset of the nonthermal HXR emission. Remarkably, the X-ray spectra of these coronal sources at the early phase were nicely fit as purely thermal.…”
Section: Introductionmentioning
confidence: 99%
“…Weak HXR emission is sometimes observed in preflares (Benz et al, 1983;Siarkowski, Falewicz, and Rudawy, 2009). Battaglia, Fletcher, and Benz (2009) reported four preflares with only thermal X-ray emission in RHESSI observations. However, Altyntsev et al (2012) searched for non-thermal emission of these events in more sensitive radio observations and found nonthermal radiation in two of these preflares using the Nobeyama Radioheliograph at 17 GHz and other radio instruments.…”
Section: Introductionmentioning
confidence: 99%